1997
DOI: 10.1038/sj.onc.1201358
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-negative CREB inhibits tumor growth and metastasis of human melanoma cells

Abstract: The ATF/CREB family of eukaryotic transcription factors contain the bZIP structural motif and mediate their transcriptional activities via heterodimerization with ATF and AP-1 family members. Quenching of CREBassociated proteins by a dominant-negative CREB (KCREB) that is mutated within its DNA-binding domain decreases radiation resistance of human melanoma cells. The purpose of this study was to determine the role of CREB in tumor growth and metastasis of human melanoma using KCREB. Highly metastatic MeWo hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 18 publications
6
122
0
Order By: Relevance
“…CREB, a critical regulator of immediate early gene transcription, has been shown to be activated by growth factors (33) and play an important role in the acquisition of the metastatic phenotype of human melanoma cells (21). Although the exact mechanism of action remains to be elucidated, our results suggest that the CRE-decoy oligonucleotides may provide a powerful means of combating cancers by regulating the expression of cAMP-sensitive genes.…”
Section: Fig 1 Cre-decoy Oligonucleotide Competes With Cre Enhancermentioning
confidence: 77%
“…CREB, a critical regulator of immediate early gene transcription, has been shown to be activated by growth factors (33) and play an important role in the acquisition of the metastatic phenotype of human melanoma cells (21). Although the exact mechanism of action remains to be elucidated, our results suggest that the CRE-decoy oligonucleotides may provide a powerful means of combating cancers by regulating the expression of cAMP-sensitive genes.…”
Section: Fig 1 Cre-decoy Oligonucleotide Competes With Cre Enhancermentioning
confidence: 77%
“…On the other hand, CREB, and additional family members such as ATF1, may contribute to melanoma cell viability (111). Interference with CREB function by ectopic expression of a dominant negative variant, capable of sequestering endogenous CREB as well as other associated proteins away from DNA sites, decreased radiation resistance of the human melanoma cell line MeWo by 3-10-fold (111), as well as their tumorigenic and metastatic potential in nude mice compared with parental controls (112). However, growth properties in vitro were not altered.…”
Section: Signal Transduction: Immediate Eventsmentioning
confidence: 99%
“…Recent evidence supports the belief that a variety of transcription factors are important in the pathogenesis of melanoma, including activating transcription factor-1 (ATF-1) (Bohm et al, 1995;, cAMP response elementbinding protein (CREB) Jean et al, 1998b;Rutberg et al, 1994;Xie et al, 1997b), transcription factor AP-2 (Huang et al, 1998;Jean et al, 1998a), micropthalmia transcription factor (Mitf) (Goding, 2000;King et al, 1999;Fang and Setaluri, 1999), and nuclear factor-kappa B (NF-kB) . In particular, we have previously demonstrated that the transition of melanoma to the metastatic phenotype is associated with a loss of expression of the transcription factor AP-2 (Bar- Eli, 1997Eli, , 1999).…”
Section: Introductionmentioning
confidence: 99%
“…After cell debris was removed by centrifugation, cell extracts were assayed for Renilla luciferase activity using the dual luciferase reporter assay system (Promega, Madison) or b-gal activity. Samples were normalized to the same relative luciferase or b-gal activity and assayed for CAT activity (Xie et al, 1997b). The cell extracts were incubated with 0.025 mCi of [14-C]chloramphenicol and 0.35 mM acetylcoenzyme A (Sigma, St. Louis, MO, USA) in 25 mM TrisHCl, pH 7.9, for 2 h at 378C.…”
Section: Transient Transfection and Cat Assaysmentioning
confidence: 99%